Pengaruh Kualitas Produk, Kualitas Pelayanan Dan Promosi Terhadap Kepuasan Konsumen Pada Soto Seger Rempah Warung Sahabat Muda Malang - Khairun Anisah; Eka Farida; Mohamad Bastomi (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract This study aims to examine and explain the effect of product quality, service quality and promotion on consumer satisfaction at the Soto Seger Spice Warung Sahabat Muda Malang. The sample used in this study was 75 respondents using the Malhotra method of porposive sampling technique. The data analysis method used in this study is quantitative data analysis using multiple linear regression analysis. Testing the data used is a partial hypothesis testing (t test). The results of this study indicate that partially (t test) the variables of product quality and service quality have a significant positive effect on customer satisfaction at the soto seger spice stalls Sahabat Muda Malang, the promotion variable has no significant effect on customer satisfaction at the Soto Seger Spices stalls Sahabat Muda Malang. Keywords: Product & Service Quality, Promotion, Satisfaction.